PRESUPPOSITIONS IN SATU INDONESIA TELEVISION PROGRAM INTERVIEW - Rizkya Fajarani Bahar; Lisetyo Ariyanti (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2020)
Interview is the way to give information from the speaker to the listener. In doing an interview, the speaker presupposes her statement to give another meaning behind what was stated. This study was aimed to analyze the presupposition type used by Tri Rismaharini as a guest star in Satu Indonesia television program interview. Also, the pragmatic functions theory which is used in advertising language was used to examine the function of the presupposition. The result found four types of presupposition which had function as emphasis, persuasive and euphemism in the pragmatic function. Those presuppositions were used to give new information to the listener as an addition from the information they had known and showed the speaker’s good attitude by delivering her statement politely. Keywords: presupposition, pragmatic, interview